2012
DOI: 10.1021/jp303794s
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Trilysine: A Model System for Understanding the Nonrandom Structure of Poly-l-lysine and Lysine-Containing Motifs in Proteins

Abstract: It is now well-established that different amino acid residues can exhibit different conformational distributions in the unfolded state of peptides and proteins. These conformational propensities can be modulated by nearest neighbors. In the current study, we combined vibrational and NMR spectroscopy to determine the conformational distributions of the central and C-terminal residues in trilysine peptides in aqueous solution. The study was motivated by earlier observations suggesting that interactions between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 77 publications
(176 reference statements)
1
24
0
Order By: Relevance
“…Previous studies by us4j,k,n,o, 7d, 13, 14 and others4c,g,l,m, 5a,b, 10b, 15 have clearly shown that, within the unfolded state, amino acid residues have unique and restricted conformational biases. Here we examine the mutual effect of unlike residues (x and y, Table 1) on residue‐level conformational bias through a combined analysis of vibrational and NMR results for GxyG peptide motifs.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies by us4j,k,n,o, 7d, 13, 14 and others4c,g,l,m, 5a,b, 10b, 15 have clearly shown that, within the unfolded state, amino acid residues have unique and restricted conformational biases. Here we examine the mutual effect of unlike residues (x and y, Table 1) on residue‐level conformational bias through a combined analysis of vibrational and NMR results for GxyG peptide motifs.…”
Section: Resultsmentioning
confidence: 86%
“…A limited set of recent experiments on homotripeptides in our laboratories revealed that interactions between like‐residues in AAA, VVV, DDD and KKK lead to a further stabilization of the already preferred conformation of the central residue. For instance, the relatively high intrinsic β‐strand propensity found for valine is increased further in VVV,9 whereas the high pPII propensity for alanine and lysine is further increases in AAA5e and KKK 7d. In addition, the unusually high turn preference for protonated aspartic acid are further increased for the central residue in DDD relative to GDG 6a.…”
Section: Introductionmentioning
confidence: 98%
“…5-7, 10, 24-26, 47-49, 89 Experimental work on e.g. AAA, the classical model system of unblocked tripeptides, essentially agrees in suggesting a large pPII content of its conformational distribution.…”
Section: Resultsmentioning
confidence: 77%
“…3-5, 10-12, 20-22 Moreover, it has become clear that amino acid residues show different conformational distributions, which can be altered by the nearest neighbors. 3, 22-26 In this context, polyproline II (pPII) has emerged as the dominant conformation for alanine, 10 whereas the pPII propensity of other residues is still a matter of a controversial debate. 3, 10, 11, 27 The canonical pPII conformation with (φ,ψ)=(−75°, 150°) is adopted by residues in trans -polyproline where it brings about a 3 1 -helix structure of the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study we combine IR, polarized Raman, VCD and 1 H NMR to examine the conformational preferences of histidine in different protonation states of GHG . Our data confirm that H has a comparatively high preference for β‐strand structures, which is only slightly modified by the protonation of the C‐terminal carboxylate group at room temperature.…”
Section: Introductionmentioning
confidence: 52%